The links between supply chain risk management practices, supply chain integration and supply chain performance in Southern Vietnam: A moderation effect of supply chain social sustainability - Ngoc Hong Duong; Quang-An Ha (Cogent Business & Management, 2021)
This research examines the impact of supply chain risk management on supply chain integration, supply chain performance, and the moderation effects of supply chain social sustainability on these relationships. The results showed that supply chain risk management has a significant impact on supplier integration, internal integration, and customer integration. However, only supplier integration and internal integration significantly impact supply chain performance, while the relationship between customer integration and supply chain performance is not significant. The moderation effects of supply chain social sustainability positively enhance the impact of supply chain risk management on supplier integration and customer integration, while it reduces the impact of supply chain risk management on internal integration. The theoretical and practical implications are also provided in the current study.
Keywords: 650; Supply chain performance; supply chain social sustainability; risk management; supply chain integration